A simple and rapid high-performance liquid chromatographic method for determining tobramycin in pharmaceutical formulations by direct UV detection - Ruckmani, K. (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: Tobramycin, an aminoglycoside antibiotic, is a polar pharmaceutical compound which lacks a UV absorbing chromophore. Due to the absence of a UV absorbing chromophore and high polar nature of this antibiotic, the analysis of such compounds becomes a major challenge. OBJECTIVE: To overcome these problems, a novel method for the determination aminoglycoside tobramycin was developed and validated based on reversed-phase high-performance liquid chromatography (RP-HPLC) with UV detector. MATERIALS AND METHODS: An isocratic mobile phase consists of buffer 0.05 M diammonium hydrogen phosphate, pH adjusted to 10.0 using tetramethyl ammonium hydroxide. Chromatography was carried out at 25°C on a Purosphere RP-8e, 250 mm × 4.6 mm, 5mm. The detection was carried out using variable wavelength UV-Vis detector set at 210 nm. The compounds were eluted isocratically at a steady flow rate of 1.0 mL/min. RESULT AND DISCUSSION: Tobramycin retention time was about 9.0 min with an asymmetry factor of 1.4. A logarithmic calibration curve was obtained from 0.47 to 0.71 mg/mL (r > 0.9998). Within-day %RSD was 0.29 (n = 6, 0.60 mg/mL) and between-day %RSD was 0.54 Specificity/ selectivity experiments revealed the absence of interference from excipients, recovery from spiked samples was between 99.0–100.0 percent. CONCLUSIONS: A HPLC method based on UV detection has been developed and validated for determination of tobramycin from ophthalmic solution. The method is simple, rapid, specific, accurate (error 0.80%), precise (RSD <2.0%) and linear (r2=0.9998). The described method is suitable for routine analysis and quality control of ophthalmic solution containing tobramycin.